I Am So Tired… How Fatigue May Exacerbate Stress Reactions to Psychological Contract Breach - Achnak, Safâa; Griep, Yannick; Vantilborgh, Tim (Frontiers in Psychology, 2018)
Abstract: Previous research showed that perceptions of psychological contract (PC) breach have undesirable individual and organizational consequences. Surprisingly, the PC literature has paid little to no attention to the relationship between PC breach perceptions and stress. A better understanding of how PC breach may elicit stress seems crucial, given that stress plays a key role in employees’ physical and mental wellbeing. Based on Conservation of Resources Theory, we suggest that PC breach perceptions represent a perceived loss of valued resources, subsequently leading employees to experience higher stress levels resulting from emerging negative emotions. Moreover, we suggest that this mediated relationship is moderated by initial levels of fatigue, due to fatigue lowering the personal resources necessary to cope with breach events. To tests our hypotheses, we analyzed the multilevel data we obtained from two experience sampling designs (Study 1: 51 Belgian employees; Study 2: 53 US employees). Note that the unit of analysis is ‘observations’ rather than ‘respondents’, resulting in an effective sample size of 417 (Study 1) and 374 (Study 2) observations. In both studies, we found evidence for the mediating role of negative emotions in the PC breach—stress relationship. In the second study, we also found evidence for the moderating role of fatigue in the mediated PC breach—stress relationship. Implications for research and practice are discussed.